Analysis of The Influence of Digital Advertising Attractiveness, User Satisfaction, and Digitalization Perceive Ease of Use on User Loyalty of Digital Payment Card E-Money - Sudirjo, Frans; Binsar Kristian Panjaitan, Feliks Anggia; Yuniarti Utami, Eva; Judijanto, Loso; Widarman, Agung (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to examine if e-money users' loyalty is influenced by promotional attractiveness, satisfaction, and convenience. The people that use electronic money make up the group that this study used. Purposive sampling was the method employed in this study, and the sample size was one hundred participants. The measurement tools used in this study are ordered according to a Likert scale. In order to collect data for this study, questionnaires and a literature review were employed. Multiple linear regression analysis was employed in this study's data analysis. The following conclusions can be made in light of the analysis and conversation: According to the partial regression test (t-test) results, convenience, satisfaction, and the attractiveness of the campaign all significantly affect the loyalty of e-money users. It is known from the simultaneous regression (f-test) results that convenience, satisfaction, and promotional attractiveness all significantly affect e-money user loyalty at the same time. Then, because it has a higher value than the convenience and happiness variables, the promotion attractiveness variable has the most prominent influence on the loyalty of e-money users.